2021
DOI: 10.1016/j.jinf.2021.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of outcomes in HIV-positive and HIV-negative patients with COVID-19

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 31 publications
1
29
0
4
Order By: Relevance
“…938 articles remained after removal of duplicates, and after screening by title and abstract, 63 articles remained. A total of 20 articles [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] met the inclusion criteria and hence were included in our analysis; 43 articles were removed, with reason. Figure 1 shows the entire screening process for this review.…”
Section: Resultsmentioning
confidence: 99%
“…938 articles remained after removal of duplicates, and after screening by title and abstract, 63 articles remained. A total of 20 articles [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] met the inclusion criteria and hence were included in our analysis; 43 articles were removed, with reason. Figure 1 shows the entire screening process for this review.…”
Section: Resultsmentioning
confidence: 99%
“…We have read with interest the article of Venturas et al, who found persons living with HIV (PWH) are not at higher risk of moderate or severe COVID-19 than the general population ( 1 ). The immune response against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in PWH is a matter of controversy and intense research, as HIV infection may impair the immune response to SARS-CoV-2 ( 2 ).…”
Section: Dear Editormentioning
confidence: 99%
“…This study adds to the growing literature describing the complex interplay between HIV and COVID‐19 [ 6 , 7 , 9 , 11 , 12 , 14 , 16 , 28 ]. The ISARIC findings [ 7 ] suggest that PLWH had an age‐adjusted 47% increased risk of mortality by day 28, which increased to 100% after adjustment.…”
Section: Discussionmentioning
confidence: 92%
“…Apart from the OPENSAFELY cohort in the UK [ 6 ], these studies were not able to adjust for socio‐economic deprivation. Conversely, cohorts matched for various confounders [ 10 , 11 , 12 , 13 ] and an unmatched cohort from South Africa [ 14 ] have not shown an increased risk of severe disease in PLWH.…”
Section: Introductionmentioning
confidence: 99%